Efficiency of four solutions in removing 23 conventional antineoplastic drugs from contaminated surfaces. - Nicolas Simon (PLoS ONE, 2020)
Background Residual contamination by intravenous conventional antineoplastic drugs (ICAD) is still a daily issue in hospital facilities. This study aimed to compare the efficiency (EffQ) of 4 different solutions to remove 23 widely used ICADs from surfaces. Method and findings A solution containing 23 ICADs (4 alkylating agents, 8 antimetabolites, 2 topo-I inhibitors, 6 topo-II inhibitors and 3 spindle poisons) was spread over 100 cm2 stainless steel. After drying, decontamination was carried out using 10×10 cm wipes moistened with 300 μL of one of the following solutions: 70% isopropanol (S1); ethanol-hydrogen peroxide 91.6-50.0 mg/g (S2); 10-2 M sodium dodecyl sulphate/isopropanol 80/20 (S3) or 0.5% sodium hypochlorite (S4). Six tests were performed for each decontamination solution. Two modalities were tested: a single wipe motion from top to bottom or vigorous wiping (n = 6 for each modality). Residual contamination was measured with a validated liquid chromatography with tandem mass spectrometry detection method. Solution efficiency (in %) was computed as follows: EffQ = 1-(quantity after decontamination/quantity before decontamination), as median (min-max) for the 23 ICADs. The overall decontamination efficiency (EffQ) of the 4 solutions was compared by a Kruskall-Wallis test. Decontamination modalities were compared for each solution and per ICAD with a Mann-Whitney test (p<0.05). EffQ were significantly different from one solution to the next for single wipe motion decontamination: 79.9% (69.3-100), 86.5% (13.0-100), 85.4% (56.5-100) and 100% (52.9-100) for S1, S2, S3 and S4 (p<0.0001), respectively. Differences were also significant for vigorous decontamination: EffQ of 84.3% (66.0-100), 92.3% (68.7-100), 99.6% (84.8-100) and 100% (82.9-100) for S1, S2, S3 and S4, respectively (p<0.0001). Generally, vigorous decontamination increased EffQ for all tested solutions and more significantly for the surfactant. Conclusion Decontamination efficiency depended on the solution used but also on the application modality. An SDS admixture seems to be a good alternative to sodium hypochlorite, notably after vigorous chemical decontamination with no hazard either to materials or workers.